2015
DOI: 10.1093/ajh/hpv093
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Exposure and Cardiovascular Hemodynamic Parameters Among Male Workers Involved in Mosquito Control in East Coast of Malaysia

Abstract: Chronic mix-pesticide exposure among workers involved in mosquito control has possible association with depression of diazoxonase and the increase in ox-LDL, brachial and aortic DBP and SBP, and heart rate. This study raises concerns that those using pesticides may be exposed to hitherto unrecognized CVS risks among others. If this is confirmed by further studies, greater efforts will be needed to protect these workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…Dioxins are believed to initiate blood pressure changes through the endothelial aryl hydrocarbon receptor (AhR), but this mechanism has been proved only in an animal model [47]. Samsuddin et al (2015) [48] reported that chronic mixed pesticide exposure among workers involved in mosquito control was possibly associated with depression of diazoxonase and an increase in oxidized low-density lipoproteino (x-LDL), brachial and aortic diastolic BP, systolic BP, and heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…Dioxins are believed to initiate blood pressure changes through the endothelial aryl hydrocarbon receptor (AhR), but this mechanism has been proved only in an animal model [47]. Samsuddin et al (2015) [48] reported that chronic mixed pesticide exposure among workers involved in mosquito control was possibly associated with depression of diazoxonase and an increase in oxidized low-density lipoproteino (x-LDL), brachial and aortic diastolic BP, systolic BP, and heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…In this study there was no significant differences in abnormal blood pressure between conventional and organic farmers. However, Samsuddin et al (2016) found that mosquito control workers with chronic mixed pesticide exposure had significantly higher brachial and aortic diastolic and systolic blood pressure levels compared to the control group [36]. POP exposure may contribute to excess adiposity and other forms of metabolism dysfunction [31].…”
Section: Discussionmentioning
confidence: 99%
“…Among experimental studies, rats were found to have increases in systolic, diastolic, and mean blood pressure for up to 56hrs after administration of chlorpyrifos (Gordon and Padnos, 2000; Smith and Gordon, 2005). Among human studies, adult male mosquito control workers in Malaysia with self-reported exposure to pesticides were found to have increased heart rate, and elevated aortic and brachial SBP and DBP (Samsuddin et al, 2016). Among Sicilian women, the incidence of gestational hypertension was twice as high among women occupationally exposed to pesticides (12%) compared to those who had indirect or domestic exposures (6% and 7% respectively), and four times greater than the incidence among unexposed women (4%).…”
Section: Discussionmentioning
confidence: 99%
“…Pesticide exposures appear to affect the cardiovascular system, and could increase the risk for cardiovascular conditions including arrhythmia, coronary artery disease, and congestive heart failure (Hung et al, 2015). High blood pressure is an important risk factor for cardiovascular disease (Kannel, 2000; Rapsomaniki et al, 2014) and a limited number of studies have described associations between history of pesticide exposures and blood pressure in children and adults (Gordon and Padnos, 2000; Grandjean et al, 2006; Samsuddin et al, 2016; Smith and Gordon, 2005; Suarez-Lopez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation